Dysregulated expression of microRNAs and mRNAs in pulmonary artery remodeling in ascites syndrome in broiler chickens - Liu, Ping (Oncotarget, 2016)
Ascites syndrome (AS), also known as pulmonary artery hypertension, remains a challenging disease that severely affects both humans and broiler chickens. Pulmonary artery remodeling presents a key step in the development of AS. In this study, we obtained pulmonary artery tissues from broilers with and without AS to perform miRNA sequencing analysis, miRNA-mRNA association analysis and pathological examinations. 29 significantly differentially expressed miRNAs were found both in known and novel miRNAs with 18 up-regulated and 11 down-regulated miRNAs. Their predicted potential targets were involved in a wide range of functional clusters as indicated via GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) analyses. The upregulation of miR-155, miR-23b-3p, miR-146b-5p and miR-146b-3p were found closely associated with the pathogenesis of pulmonary artery remodeling in AS progression. The association analysis for the miRNAs-mRNAs showed that these 29 significantly differentially expressed miRNAs regulate 162 differentially expressed target genes. Among them, 20 miRNAs correlated with 18 predicted target genes that appear to be involved in pulmonary artery remodeling, mainly in three broad physiological processes: the hypoxia sensing response (HIF1a, NHE1, STAT5 and STAT3), endothelial permeability dysfunction (CD44, TRAF2, CDK2AP1, LZTFL1, JAZF1, PEBP1, LRP1B, RPS14 and THBS2) and inflammation (MEOX2, STAT5, STAT3, IRF8, MAP3K8, IL-1BETA and TNFRSF1B). Pathological pulmonary artery remodeling in the AS broilers was consistently observed in the present study. Taken together, the current analysis further illuminates the molecular mechanism of pulmonary artery remodeling underlying AS progression.